1993
DOI: 10.1007/bf01245227
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and depression

Abstract: The dopamine hypothesis of schizophrenia and the emphasis on other neurotransmitters, most notably norepinephrine, serotonin, and acetylcholine, in the pathogenesis of depression, have focused attention away from substantial evidence implicating dopamine in affective disorders. The clinical evidence includes alterations in depressive symptoms with aging (concomitant with possible changes in dopamine metabolism), potential dopaminergic involvement in several subtypes of depression, similarities between some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(150 citation statements)
references
References 129 publications
6
136
0
4
Order By: Relevance
“…In agreement, a number of studies have shown that there is a reduced level of DA and its metabolites in the CSF of depressed patients (Brown and Gershon, 1993) and also a reduced release and metabolism of DA in the basal ganglia of animals subjected to stressors that induce behavioral depression (Cabib and Puglisi-Allegra, 1996). This reduction, however, does not appear to be caused by a direct impairment of the dopaminergic neurons or postsynaptic receptors themselves (Weiss et al, 1996;Cabib et al, 1998;Ossowska et al, 2001;Herman et al, 1984;ZebrowskaLupina et al, 1988), but may occur instead in an afferent system that modulates dopaminergic function.…”
Section: Role Of a 1 -Adrenoceptors In Behavioral Activitysupporting
confidence: 69%
“…In agreement, a number of studies have shown that there is a reduced level of DA and its metabolites in the CSF of depressed patients (Brown and Gershon, 1993) and also a reduced release and metabolism of DA in the basal ganglia of animals subjected to stressors that induce behavioral depression (Cabib and Puglisi-Allegra, 1996). This reduction, however, does not appear to be caused by a direct impairment of the dopaminergic neurons or postsynaptic receptors themselves (Weiss et al, 1996;Cabib et al, 1998;Ossowska et al, 2001;Herman et al, 1984;ZebrowskaLupina et al, 1988), but may occur instead in an afferent system that modulates dopaminergic function.…”
Section: Role Of a 1 -Adrenoceptors In Behavioral Activitysupporting
confidence: 69%
“…There is a high comorbidity with each of these factors and problem gambling Specker et al, 1995). Moreover, each of these disorders involves disturbances in neurochemical systems activated by psychostimulant drugs (Brown and Gershon, 1993;Solanto, 2002). Therefore, it remains to be determined if the present findings extend to such cases.…”
Section: Limitationsmentioning
confidence: 87%
“…A positive mood can be gained through the forced laugh, and a bad mood, personality, or thought can be changed somewhat into a positive direction (Isen and Means 1983). According to the latest precedent studies, reduction in secretion of the neurotransmitters, dopamine and serotonin, is the representative of one of the many causes of depression; therefore, if the secretion of those substances reduces, there will be a disorder in mood control in the brain and depression will develop (Brown and Gershon 1993). However, a positive attitude and forced laughter can help maintain dopamine activity (Ashby et al 1999).…”
Section: Laughter and Depressionmentioning
confidence: 99%